Professor Emeritus, Prof. Dr. Dr. h.c. Niko Torelli - Primož Oven (Les, 2020)
At the end of 2020, Prof. Dr. Dr. h.c. Nikolaj Torelli became a Professor Emeritus of the University of Ljubljana. The title of Professor Emeritus is awarded to retired Professors for their significant contributions to the operation, reputation, and development of the University of Ljubljana. We briefly introduce our new Professor Emeritus and his work.